2020
DOI: 10.3390/brainsci10060392
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Connectome-based Electrophysiological Study of Subjective Cognitive Decline Related to Alzheimer’s Disease by Using Resting-state High-density EEG EGI GES 300

Abstract: Aim: To investigate for the first time the brain network in the Alzheimer’s disease (AD) spectrum by implementing a high-density electroencephalography (HD-EEG - EGI GES 300) study with 256 channels in order to seek if the brain connectome can be effectively used to distinguish cognitive impairment in preclinical stages. Methods: Twenty participants with AD, 30 with mild cognitive impairment (MCI), 20 with subjective cognitive decline (SCD) and 22 healthy controls (HC) were examined with a detailed neuropsycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 143 publications
(222 reference statements)
2
18
0
Order By: Relevance
“…Previous EEG studies exploring AD brain connectomics showed discordant results, basically due to different methodological approaches, which complicates the comparability of obtained results ( Vecchio et al, 2017 , Xie and He, 2011 , Lazarou et al, 2020 , Tijms et al, 2013 ). Among others, for instance, one study applied linear lagged coherence to eLORETA solutions extracted from a population of AD, MCI and healthy subjects, describing network reconfiguration profiles which are only partially in line with our findings ( Vecchio et al, 2014 , Vecchio et al, 2015 ); in parallel with an increased normalized clustering coefficient in theta band in MCI and AD patients, indeed, they also described an increased normalized path length.…”
Section: Discussionmentioning
confidence: 99%
“…Previous EEG studies exploring AD brain connectomics showed discordant results, basically due to different methodological approaches, which complicates the comparability of obtained results ( Vecchio et al, 2017 , Xie and He, 2011 , Lazarou et al, 2020 , Tijms et al, 2013 ). Among others, for instance, one study applied linear lagged coherence to eLORETA solutions extracted from a population of AD, MCI and healthy subjects, describing network reconfiguration profiles which are only partially in line with our findings ( Vecchio et al, 2014 , Vecchio et al, 2015 ); in parallel with an increased normalized clustering coefficient in theta band in MCI and AD patients, indeed, they also described an increased normalized path length.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety-eight AD patients were included, who met the National Institute of Neurological and Communication Disorders and Stroke/Alzheimer’s Disease and Related Disorders Association (NINCDS-ADRDA) criteria for probable AD [13]. Patients with chronic kidney disease, heart disease, diabetes, vascular dementia, and other neurodegenerative dementia, previous history of depression or schizophrenia, receiving drugs to improve neurocognitive function, hearing loss, blindness, and severe speech disorders were excluded from the study.…”
Section: Methodsmentioning
confidence: 99%
“…Our recent review [ 94 ] suggested that SCD may actually demonstrate intermediate changes between healthy elders and MCI at a network level of the brain and implies that brain connectome could be considered as a potential biomarker of predicting future cognitive deterioration associated with AD. However very limited studies have so far explored the brain network in SCD using EEG [ 93, 94 ]. In the majority of the included studies, SCD exhibited lower values compared to healthy controls with regards to local efficiency, network strength, and shortest path length but preserved global network properties such as small-world and rich-club.…”
Section: Introductionmentioning
confidence: 99%